2017
DOI: 10.1167/iovs.16-21163
|View full text |Cite
|
Sign up to set email alerts
|

Losartan Attenuates Scar Formation in Filtering Bleb After Trabeculectomy

Abstract: PURPOSE.To examine the effects of losartan on scar formation after trabeculectomy and on fibrotic changes of human Tenon's fibroblasts (HTFs). METHODS.Trabeculectomy was performed on New Zealand rabbits. They were randomized to receive one of the following treatments: 0.9% normal saline, mitomycin-C, or one of the three doses of losartan. Bleb morphology, IOP, and histopathology examination were performed. Primary cultured HTFs were treated with losartan or vehicle, with or without angiotensin II (Ang II). Cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…In their study, losartan (10 –5 M) decreased HTF cell proliferation compared to the control by 20.4%, migration by 48.3% at 24 hours, and transdifferentiation and ECM (extracellular matrix) synthesis by almost 2-fold. 31 Additionally, they also indicated that losartan (5 mg/mL) attenuated bleb scarring after trabeculectomy in rabbit eyes with a 77.8% inhibition compared to control. 31 …”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…In their study, losartan (10 –5 M) decreased HTF cell proliferation compared to the control by 20.4%, migration by 48.3% at 24 hours, and transdifferentiation and ECM (extracellular matrix) synthesis by almost 2-fold. 31 Additionally, they also indicated that losartan (5 mg/mL) attenuated bleb scarring after trabeculectomy in rabbit eyes with a 77.8% inhibition compared to control. 31 …”
Section: Discussionmentioning
confidence: 96%
“…A previous study 30 established the promoting effect of Ang II on fibrosis in vivo after trabeculectomy in rabbits and in vitro using HTFs. Since then, Shi et al 31 also showed that losartan attenuated scar formation in vivo and in vitro. In their study, losartan (10 –5 M) decreased HTF cell proliferation compared to the control by 20.4%, migration by 48.3% at 24 hours, and transdifferentiation and ECM (extracellular matrix) synthesis by almost 2-fold.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations